Tradition, Authority, and Immanent Critique in Comparative Ethics. Issue 4 (December 2014) - Kellison, Rosemary B.
Abstract Drawing on resources from pragmatist thought allows religious ethicists to take account of the central role traditions play in the formation and development of moral concepts without thereby espousing moral relativism or becoming traditionalists. After giving an account of this understanding of the concept of tradition, I examine the ways in which understandings of tradition play out in two contemporary examples of tradition‐based ethics: works in comparative ethics of war by James Turner Johnson and John Kelsay. I argue that a pragmatist approach to tradition‐based ethics allows for a nuanced and flexible understanding of moral traditions, and one that holds great promise for international consensus‐building around shared ethical norms for the use of armed force.